Locoregional methods of treatment of patients with extrahepatic bile duct cholangiocarcinoma (review of literature) - S. Y. Ivanusa; S. A. Alentev; D. Y. Evstrateva; A. A. Molchanov (Вестник хирургии имени И.И. Грекова)
The article presents a literature review of studies on the use of local destruction methods (photodynamic therapy and radiofrequency ablation) in the treatment of patients with unresectable extrahepatic cholangiocarcinoma. Currently, many studies have been published on the assessment of photodynamic therapy in the treatment of patients of this category. Radiofrequency ablation in tumors of extrahepatic bile ducts has been used relatively recently, but, according to available data, it may represent an alternative to photodynamic therapy. The article discusses the mechanism of action, the method of photodynamic therapy and radiofrequency ablation, and presents the results of the largest studies. It is reported that photodynamic therapy is comparable to R1/R2 resection according to the survival results. There is evidence of its successful use as adjuvant and neoadjuvant treatment, the possibility of using photodynamic therapy as a method of local tumor control in patients with unresectable cholangiocarcinoma awaiting liver transplantation. The use of radiofrequency ablation at the first stage before stenting the biliary tract allows to increase the diameter of the bile ducts, increases the stent patency time, as well as the survival orate f patients. In addition, radiofrequency ablation and photodynamic therapy can be successfully applied to occlude previously inserted stents. The advantage of photodynamic therapy is the possibility of using it in weakened patients with hyper bilirubinemia. The advantages of radiofrequency ablation include the lower cost of the procedure, as well as the absence of the need to keep the light regimen. The prospects of using methods of locoregional destruction as part of combined treatment regimens (in combination with systemic or regional chemotherapy) are being studied, which allows achieving the best results.